Closing Research Investment Gaps for a Global Food Transformation - Bollington, Alex; DeLonge, Marcia; Mungra, Dhara; Hayek, Matthew; Saifuddin, Mustafa; McDermid, Sonali Shukla (Frontiers in Sustainable Food Systems, 2021)
Recent calls for a global food transformation have centered on simultaneously improving human and environmental health, recognizing that food and nutrient diversity have declined over time while food systems have exacted a heavy climate and ecological toll. Grain legumes and coarse grain crops provide important human nutrition and environmental benefits, but the production and consumption of many of these crops remains relatively low compared to major commodities, such as maize, wheat, rice, and soy. Outstanding hurdles to scaling up these “minor commodity” crops include (among other things) their relatively lower yields, and lower farmer adoption, based partly on actual or perceived profitability and marketability. We hypothesize that these limitations are attributable in part to unequal funding for these crops’ research and development (R&D) both on a national and global scale. In the United States, we show that investment patterns for a snapshot of USDA-funded research grants from 2008-2019 consistently favor major commodity crops, which received 3 to 4.5 times more funding and 3 to 5 times as many grants than the minor commodity crop groups. This current USDA funding allocation poses a barrier to food system transformations. Achieving nutritious diets for planetary health requires more public agricultural investment towards minor commodity crops and increased collaboration between public health, nutrition, agriculture, and environmental sectors.